Does NETosis Contribute to the Bacterial Pathoadaptation in Cystic Fibrosis? - Rahman, Samir; Gadjeva, Mihaela (Frontiers in Immunology, 2014)
Significant advances in our understanding of neutrophil biology were made in the past few years. The exciting discovery that neutrophils deploy neutrophil extracellular traps (NETs) to catch pathogens paved the way for a series of additional studies to define the molecular mechanisms of NET generation and the biological significance of NETosis in acute and chronic pathologic conditions. This review highlights the latest knowledge regarding NET structures, deployment, and function, with an emphasis on current understanding of NET proteomes, their conservation, and significance in the context of cystic fibrosis (CF), a condition characterized by excessive extracellular DNA/NET presence. We also discuss how our understanding of NETosis yields novel therapeutic approaches and their applicability to CF.